2014
DOI: 10.1002/ccr3.107
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous delivery through a cervical tear without cervical os dilatation

Abstract: Key Clinical MessageSpontaneous delivery through a cervical tear, provoked by prostaglandin-induced uterine contractions, was described in a G2P0 woman with a history of cervical dilatation and uterine curettage. This rare complication with potentially serious maternal–fetal consequences can be predicted by an aberrant cervical response to prostaglandins in parturients with previous cervical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…3 The known precipitating factors for CL in literature being previous interventions on the cervix 6-14% (polypectomy, LEEP, cerclage), induction of labour (threefold increased risk), use of Prostaglandins for induction of labour, precipitate labour, operative vaginal deliveries and birth weight > 3500gms. [1][2][3][4][5] However, in our experience of the known risk factors, the most common association were with induction of labour and operative vaginal delivery. In recent years the rate of induction of labour have exponentially increased.…”
Section: Discussionmentioning
confidence: 91%
“…3 The known precipitating factors for CL in literature being previous interventions on the cervix 6-14% (polypectomy, LEEP, cerclage), induction of labour (threefold increased risk), use of Prostaglandins for induction of labour, precipitate labour, operative vaginal deliveries and birth weight > 3500gms. [1][2][3][4][5] However, in our experience of the known risk factors, the most common association were with induction of labour and operative vaginal delivery. In recent years the rate of induction of labour have exponentially increased.…”
Section: Discussionmentioning
confidence: 91%
“…Djokovic et al . reported a spontaneous delivery through a cervical tear provoked by prostaglandin-induced uterine contractions in a G2P0 woman with a history of cervical dilatation and uterine curettage [ 6 ]. Singhal et al reported the first two cases of bucket-handle cervical tears in a second trimester unscarred uterus after misoprostol use [ 7 ], and Abubeker et al .…”
Section: Discussionmentioning
confidence: 99%
“…During the serial digital examinations of the cervical response during induction of labor, particular attention should be paid to the characteristics and modification of the external os. Upon completion of cervical effacement and in the presence of significant uterine contractility, repetitive findings of a rigid external os should be considered as an alarm signal [ 6 ]. Our case was in the latent phase of labor throughout the induction of labor.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Smith et.al , showed that these tears were closely related to shoulder dystocia, episiotomy, prolonged second stage of labour, macrosomic baby and instrumental delivery [13] . In nulliparous women at term, external cervical os remains stationary during the cervical shortening, but it quickly evolves once the cervical effacement is completed [14] .…”
Section: Discussionmentioning
confidence: 99%